Simple, rapid and reliable methods to obtain high quality RNA and genomic DNA from Quercus ilex L. leaves suitable for molecular biology studies (Acta Physiologiae Plantarum, 2011)
Isolation of high-quality RNA and genomic DNA (gDNA) from many samples is a necessary step before accomplishing molecular biology studies. The particular composition of Quercus ilex leaves, specially hard and rich in cell wall material, polyphenolics and secondary metabolites, usually results in preparations contaminated with non-nucleic acid compounds. Although many methods have been developed, each case of study demands a protocol adapted to the speciﬁc plant sample and the pursued research objectives. We have evaluated several protocols to establish the methodology that best suited to our current genetic and molecular studies on Q. ilex. Our priority was to select the simplest methods reducing the plant starting material and the time employed, without compromising yield, quality and integrity of the isolated nucleic acids. Our results point to two protocols based on silicamembrane puriﬁcation, as the most convenient for Q. ilex leaf tissue, and both procedures are greatly improved by adding insoluble polyvinyl polypyrrolidone during the isolation process. The protocols optimized here can be completed at the microfuge scale and allow a researcher to process 48 samples in 1 h, producing high quality preparations suitable for the routinely molecular biology applications with higher efﬁciency than other more labour and time-consuming protocols

Changes in the protein profile of Quercus ilex leaves in response to drought stress and recovery. - Echevarría-Zomeño, Sira; Ariza, David; Jorge, Inmaculada; Lenz, Christof; Del Campo, Antonio; Jorrín, Jesús V.; Navarro, Rafael M. (Journal of plant physiology, 2009)
To characterize the molecular response of holm oak to drought stress and its capacity to recover 9-month-old Quercus ilex seedlings were subjected to three treatments for a 14-d period: (i) continuous watering to field capacity (control plants, W), (ii) no irrigation (drought treatment, D), and (iii) no irrigation for 7d followed by a watering period of 7d (recovery treatment, R). In drought plants, leaf water potential decreased from -0.72 (day 0) to -0.99MPa (day 7), and -1.50MPa (day 14). Shoot relative water content decreased from 49.3% (day 0) to 47.7% (day 7) and 40.8% (day 14). Photosystem II quantum yield decreased from 0.80 (day 0) to 0.72 (day 7) and 0.73 (day 14). Plants subjected to water withholding for 7d reached, after a 7-d rewatering period, values similar to those of continuously irrigated control plants. Changes in the leaf protein pattern in response to drought and recovery treatments were analyzed by using a proteomic approach. Twenty-three different spots were observed when comparing the two-dimensional electrophoresis profile of control to both drought and recovered plants. From these, 14 proteins were identified from tryptic peptides tandem mass spectra by using the new Paragon algorithm present in the ProteinPilot software. The proteins identified belong to the photosynthesis, carbohydrate and nitrogen metabolism, and stress-related protein functional categories.
The following values have no corresponding Zotero field: accession-num: 18778874
Keywords: Drought stress; Holm oak proteome; Mass spectrometry; Quercus ilex

Changes in the protein profile of Quercus ilex leaves in response to drought stress and recovery. (Journal of plant physiology, 2009)
To characterize the molecular response of holm oak to drought stress and its capacity to recover 9-month-old Quercus ilex seedlings were subjected to three treatments for a 14-d period: (i) continuous watering to field capacity (control plants, W), (ii) no irrigation (drought treatment, D), and (iii) no irrigation for 7d followed by a watering period of 7d (recovery treatment, R). In drought plants, leaf water potential decreased from -0.72 (day 0) to -0.99MPa (day 7), and -1.50MPa (day 14). Shoot relative water content decreased from 49.3% (day 0) to 47.7% (day 7) and 40.8% (day 14). Photosystem II quantum yield decreased from 0.80 (day 0) to 0.72 (day 7) and 0.73 (day 14). Plants subjected to water withholding for 7d reached, after a 7-d rewatering period, values similar to those of continuously irrigated control plants. Changes in the leaf protein pattern in response to drought and recovery treatments were analyzed by using a proteomic approach. Twenty-three different spots were observed when comparing the two-dimensional electrophoresis profile of control to both drought and recovered plants. From these, 14 proteins were identified from tryptic peptides tandem mass spectra by using the new Paragon algorithm present in the ProteinPilot software. The proteins identified belong to the photosynthesis, carbohydrate and nitrogen metabolism, and stress-related protein functional categories.